ARTISANAL FISHING IN NORTHEAST BRAZIL: CHALLENGES AND PERSPECTIVES - Soares De Moura, Jameson; Marcos Fontes Neto, José; Farias Souza Ciriaco Mendes, Vilck; Isabella Freitas Marquetti, Maria; Alexandre Holanda Melo, Milton; Da Silva Lacerda Jr, Orivaldo (Journal of Interdisciplinary Debates, 2025)
Artisanal fishing in Northeastern Brazil constitutes a traditional practice essential for the subsistence, cultural identity, and economy of coastal communities. However, this activity is increasingly threatened by environmental, territorial, social, and political factors. This bibliographic and exploratory study reviews and systematizes the main challenges faced by artisanal fisheries, emphasizing the impacts of marine pollution, habitat degradation, climate change, territorial conflicts, and socioeconomic vulnerabilities. The findings indicate that oil spills, the expansion of industrial and tourist enterprises, as well as pollution by heavy metals and microplastics, compromise the integrity of aquatic ecosystems and undermine the sustainability of artisanal fishing. Furthermore, disputes over resource use and the lack of effective public policies intensify the social marginalization of fishers. It is concluded that artisanal fishing faces a multifaceted process of vulnerability, which demands inclusive public policies, the strengthening of community governance, the diversification of productive activities, and the valorization of traditional knowledge.